Stress transfer using the Okada dislocation model: A case study of the Gorkha Earthquake (BIBECHANA, 2026)
We study the static Coulomb stress change (ΔCFS) produced by  2015 Gorkha earthquake using a rectangular fault model and the Okada (1992) elastic dislocation solution in a homogeneous, isotropic half-space. We tested five slip scenarios (S1–S5: 2.0–6.5 m) with a shear modulus of 30 × 10⁹ Pa and friction coefficient of 0.4. Stress fields were first computed along 1D profiles extending ±200 km from the rupture center and subsequently used to construct 2D stress maps. The results show that peak ΔCFS increases linearly with slip amplitude, with the highest-slip case (6.5 m) producing ~13 MPa at the epicenter. Regression analysis confirms a strong linear scaling (ΔCFS ≈ 2.13 × Slip, R² ≈ 0.92), indicating that each meter of slip enhances peak stress by ~2.13 MPa. The 2D stress maps reveal symmetric positive and negative lobes around the rupture, with stress decaying rapidly with distance. The longitudinal stress profiles along longitudinal demonstrate a sharp concentration of stress at the epicenter (28.147°N, 84.708°E) with symmetric decay to zero levels within about ±1.3° longitude. These findings indicate that slip amplitude primarily governs local stress concentration with short-range triggering potential, while far-field stress patterns are comparatively insensitive to variations in slip magnitude.